2013 13th IEEE-RAS International Conference on Humanoid Robots (Humanoids) 2013
DOI: 10.1109/humanoids.2013.7029999
|View full text |Cite
|
Sign up to set email alerts
|

Soft-actuators in cyclic motion: Analytical optimization of stiffness and pre-load

Abstract: In this paper, we study the role of soft actuation in the reduction of the energy cost for mechanical systems that perform cyclic tasks. The objective is to determine the optimal stiffness value and spring pre-load such that a given cost functional is minimized. For the analysis, we consider both fully actuated and underactuated mechanical systems using elastic actuators which, depending on how and where the springs are placed w.r.t. the actuator and the load, can be Series Elastic Actuators (SEAs) or Parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Comparisons between serial and parallel configurations can be found in References [84][85][86][87][88]. T. Verstraten et al in Reference [87], provide a comparison between stiff actuators, parallel elastic actuators and serial elastic actuators in terms of power as well as mechanical and electrical energy consumption.…”
Section: Discussion Of Elastic Elements Configurationsmentioning
confidence: 99%
“…Comparisons between serial and parallel configurations can be found in References [84][85][86][87][88]. T. Verstraten et al in Reference [87], provide a comparison between stiff actuators, parallel elastic actuators and serial elastic actuators in terms of power as well as mechanical and electrical energy consumption.…”
Section: Discussion Of Elastic Elements Configurationsmentioning
confidence: 99%
“…In (10) the gait is constrained to be periodic, by imposing the relation between x red (0) and x red (T h ). The additional inequality constraints, stated in (11), guarantee that the external contact wrench w belongs to the static friction cone, that the contact is unilateral and that the Center of Pressure (CoP) is inside the support area. Moreover, limits on joint positions and velocities, as well as on motor torques, are imposed.…”
Section: Appendixmentioning
confidence: 99%
“…compliance, purposefully introduced in the mechanical design to guarantee robustness [10], efficiency [11], peak performance [12], is usually neglected or not properly taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have compared SEAs and parallel-elastic actuators (PEAs), mainly in torque and power requirements. Cyclic hoppers were considered by Velasco et al (2013) and Yesilevskiy et al (2015), and exoskeleton actuation was considered by Wang et al (2011). Grimmer et al (2012) showed that combining SEA + PEA can yield further benefits.…”
Section: Introductionmentioning
confidence: 99%